ANALISIS SISTEM INFORMASI MANAJEMEN PERIZINAN PERCERAIAN ASN DI KABUPATEN SUMEDANG - Dadang Priyatna; Cecep Hasanudin; Meilani Maryam (LPPM UNSAP & FISIP UNSAP, 2021)
This study aims to find out, obtain objective data and information regarding the Analysis of Management Information Systems in the Divorce Licensing Process State Civil Apparatus (ASN) In The Staffing And Human Resource Development Agencies Sumedang District. The existence of information in an institution, including government is very complex and has an important role. One unit produces information with each other, requires information, and excanges information. The management information system contains a set of organizational procedures wich when implemented will provaid information for decision making and or for controlling the organization. The problems studied in this study are related to the management information system (SIM) and state administration Management Information System (SIM) are direted to support decision making, as well as planning and control. The position of the state administration with the Management Information System (SIM) is cosely related especially in a work that support each other to achieve a goal. The method used in this research is qualitative research methods with data collection, observation steps, in-depth interviews and documentation. From this research, there are obstacles regarding the Management Information System in the Divorce Licensing Process State Civil Apparatus (Asn) At The Staffing And tHuman Resource Development Agencies Sumedang District, namely: human resources, supporting facilities, disciplinary application, and information technology. Efforts to overcome obstacles include increasing discipline, procurement and management of facilities and infrastructure, division of labor, and management of information and data in the Divorce Licensing Process State Civil Apparatus (Asn) At The Staffing And Human Resource Development Agencies Sumedang District.